2024
DOI: 10.1002/ecj.12441
|View full text |Cite
|
Sign up to set email alerts
|

Development of a virtual reality system that generates prism adaptation for multiple motor units

Takashi Ishida,
Hiroki Higa

Abstract: Conventionally, the adaptive body area for prism adaptation (PA) has been limited to the visible area of prism glasses, especially the unilateral upper limbs. In this study, we developed a virtual reality system that extends PA's adaptive body area. This system sets the visible area of the target and introduces a symbolic representation of the body position to realize a head position adaptation task. As a result, the develped system generates PA not to individual body parts but to a collection of multiple moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…These studies report similar effects for VR and traditional PA, thus highlighting the potential benefit of a mobile device, especially for post-hospital use. Similarly, Ishida and Higa (2023 , 2024) developed a virtual prism adaptation system including posture measurement functionality, expanding the application range of prism adaptation to the whole body.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies report similar effects for VR and traditional PA, thus highlighting the potential benefit of a mobile device, especially for post-hospital use. Similarly, Ishida and Higa (2023 , 2024) developed a virtual prism adaptation system including posture measurement functionality, expanding the application range of prism adaptation to the whole body.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, some studies exhibited concerns related to bias from the measurement of exposure and post-exposure interventions. Specifically Fuji et al (2018) and Kim et al (2017) for exposure measurement, Faity et al (2023) , Ramos et al (2019) , and Ishida and Higa (2024) for post-exposure interventions. Moreover, all studies selected except four, Ishida and Higa (2023) and Ramos et al (2019) , Chen et al (2022) , and Ishida and Higa (2024) , showed a low risk of bias in the selection of participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This system may expand the use of prism adaptation to involve full-body participation, enhancing the therapeutic process by integrating postural feedback and encouraging spontaneous head orientation toward the neglected side (Ishida and Higa, 2023). The development of the VR system opens new perspectives for applying PA to a collection of multiple motor units, such as the upper trunk system, and highlights the potential of this approach for postural correction in USN patients, along with possible applications in detecting cerebellar disorders (Ishida and Higa, 2024). Future studies are needed to explore the applicability and effectiveness of this system.…”
Section: Discussionmentioning
confidence: 99%